Tracheostomy in Spinal Cord Injured Patients - Ganuza, Javier-Romero (Università di Salerno, 2011)
Patients with cervical spinal cord injury frequently need prolonged mechanical ventilation as a result of worsening pulmonary vital capacity due to paralysis of respiratory muscles, severe impairment of tracheobronchial secretions clearance and high incidence of respiratory complications like pneumonia or atelectasis. Patients with thoracic spinal cord injury may need mechanical ventilation due to associate injuries. For these reasons, tracheostomy is frequently performed in these patients, more frequently when the spinal cord injury is at cervical level. Percutaneous technique, performed in the ICU, should be considered the preferred procedure for performing elective tracheostomies in spinal cord injured patients. Tracheostomy should be implemented as soon as possible in SCI patients they require prolonged mechanical ventilation. Tracheostomy can be performed just after anterolateral cervical spine fixation surgery. Tracheostomy can be removed when no longer needed without major complications.